Credit Analysis And Credit Risk In The Indonesian Banking Industry - Sabaruddin Siagian; Faizal Roni (Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes banking credit performance and credit risk in Indonesia before, during, and after the Covid-19 pandemic. The research applies a descriptive analytical method using secondary data obtained from the Financial Services Authority (OJK), focusing on commercial banks. Before Covid-19, banking credit was in a stable condition, with normal lending and credit growth exceeding the growth of third-party funds (DPK). This indicates that banks were active in distributing credit supported by sufficient funding. When Covid-19 occurred, economic performance declined significantly, and credit distribution contracted. For three consecutive quarters, both economic growth and credit growth recorded negative figures as banks became more cautious due to shrinking business activities and rising uncertainty. In the post-pandemic period, spanning nine quarters up to Q4 2024, the banking sector showed strong recovery aligned with economic improvement. Credit growth increased sharply and was noticeably higher than DPK growth, demonstrating restored confidence and better financial intermediation capacity. Regarding credit risk, banks managed non-performing loans (NPL) effectively both before and after Covid-19, maintaining NPL ratios below the 5 percent regulatory threshold. During Covid-19, banks strengthened reserves through increased allowance for impairment losses (CKPN) to keep NPL stable, although this temporarily reduced profitability as reflected in lower return on assets (ROA). Overall, Indonesian banks showed resilience through prudent risk management.